The coronavirus conundrum - Countries better prepared to face the pandemic - The Omicron variant and mutations - New vaccines? - The pregnant woman, the placenta, the fetus and the neonate - Romero, José Pacheco (2022)
The Omicron variant has continued to advance around the world at a rate several times faster than the previous variants, with more infections, but fewer hospitalizations for severe cases and deaths than the delta variant. However, the question now arises as to what might happen with the new variant with a similar genetic background to the Delta variant, but together with 10 mutations of the Omicron, the so-called Deltacron.